Extreme-wind events in China in the past 50 years and their impacts on sandstorm variations - Jiang, Yingsha; Miao, Yunfa; Zhao, Yongtao; Liu, Jingjing; Gao, Yanhong (Frontiers in Earth Science, 2023)
Extreme-wind events not only cause disasters by themselves but can also trigger sandstorms, resulting in significant social and economic losses. Since recent years have experienced more frequent and severe extreme weather events, it is worth to explore how extreme-wind events response to recent climate change and how they impact the sandstorm variation. This work established two indices, EW90 and EW95, to identify extreme-wind events based on the relation between extreme-wind intensity and local-source sandstorm. EW90 and EW95 extreme-wind indices are defined as the daily maximum wind speeds greater than the 90th and 95th quantiles of local long-term historical records. The spatial distributions of EW90 and EW95 extreme-wind events are similar, which is higher in arid and semi-arid and coastal regions, and lower in southern China. Seasonally, extreme-wind events mainly occur in April and May for most areas over China, while they are more frequent from July to August for humid regions. During 1971–2020, both the EW90 and EW95 extreme-wind speeds and annual frequencies have significant decreasing trend (p < 0.01), while the daily mean wind speed does not decrease significantly. Extreme-wind events do not have significant abrupt change as well, while a turning positive trend after 2003 is found for mean wind speed. Moreover, sandstorm days are highly correlated with the EW90 and EW95 extreme-wind events, with linear and partial correlation coefficients around 0.95 and 0.5, respectively, while they do not have significant correlations with mean wind speed. Therefore, the significant reduction of sandstorms over northern China in the past 50 years is mainly due to the substantially decreasing extreme-wind events.